Engine-propeller matching for fishing vessel at Kuala Pahang - Muhammad Zaharin, Zakaria (2010)
Fishing vessel is a transport for fishermen to catch fish at the sea. Ship propulsion normally occurs with the help of a propeller while the propeller absorbs power from the engine to move. The propeller is depending on the engine and the ships resistance. So, whatever source of propeller power used, but it’s still depending on those factors. So, the factors will affect the speed or power performance. Thus, the right combination of engine and propeller are required to give good performance, fuel economy and others. The objective of this project is to calculate the engine-propeller matching for fishing vessel at Kuala Pahang bay. By surveying the fishing vessel at the bay, collecting some data required to proceed to other steps. From the data, the resistance of the ship and also the power of the ship are calculated. From the result, a propeller and an engine is selected to find the matching point. At the point, the power output from the engine equals to power absorb by the propeller. So, the fishing vessel was operated in high efficiency, high performance and reduces its fuel consumption.